2021
DOI: 10.1007/s00216-020-03109-2
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of the quantification approaches for the non-targeted screening of micropollutants and their transformation products in groundwater

Abstract: A wide range of micropollutants can be monitored with non-targeted screening; however, the quantification of the newly discovered compounds is challenging. Transformation products (TPs) are especially problematic because analytical standards are rarely available. Here, we compared three quantification approaches for non-target compounds that do not require the availability of analytical standards. The comparison is based on a unique set of concentration data for 341 compounds, mainly pesticides, pharmaceutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 36 publications
3
47
0
Order By: Relevance
“…Several different approaches have been tested to overcome the lack of analytical standards and evaluate the most accurate ones for the semi-quantification [ 34 ]. Two strategies, based on the assumptions that TPs have the same response as the parent compounds and that the internal standard eluting closest to the compound of interest will have a similar response factor, appeared to be less reliable when comparing to the approach based on the prediction of the ionization efficiency of the compounds in the ESI source.…”
Section: Resultsmentioning
confidence: 99%
“…Several different approaches have been tested to overcome the lack of analytical standards and evaluate the most accurate ones for the semi-quantification [ 34 ]. Two strategies, based on the assumptions that TPs have the same response as the parent compounds and that the internal standard eluting closest to the compound of interest will have a similar response factor, appeared to be less reliable when comparing to the approach based on the prediction of the ionization efficiency of the compounds in the ESI source.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been found that ionization efficiencies are correlated between different instruments [ 40 ]. This has previously enabled training a single ionization efficiency model and transferring the predictions to different instruments via correlation [ 15 ]. Therefore, the transferability of the model can be further investigated in the future, alongside validation engaging several instruments and laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations, machine learning approaches for predicting the ionization efficiency of the detected compounds have recently been developed [ 10 , 11 , 12 , 13 ]. The predicted ionization efficiencies can be further used to quantify the tentatively identified compounds if analytical standards are lacking [ 11 , 14 , 15 ]. These approaches rely on descriptors deduced from the structure of the compound and, therefore, at minimum a tentatively known structure of the detected compound is required.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that deciding on the size and composition of a sufficient ISTD set for intensity normalization is difficult, as the compounds in the environmental sample are initially unknown to the investigator and a large structural variety can be expected. Moreover, the factors influencing the RT and the ionization efficiency are to some extent different 70,71 …”
Section: Prioritizationmentioning
confidence: 99%